Antecedents to consumers' showrooming behaviour: an integrated TAM-TPB framework. Issue 4 (11th June 2018) - Arora, Sourabh; Sahney, Sangeeta
Abstract : Purpose: The purpose of this study is to propose an integrated framework utilizing the theory of planned behaviour (TPB) and technology acceptance model (TAM) to augment the understanding on consumers' showrooming behaviour. Design/methodology/approach: Selective sampling was used for data collection. The integrated TAM-TPB framework led to 12 propositions, which were tested using partial least squares-structural equation modelling. Findings: Both perceived relative search benefits offline and relative purchase benefits online significantly determined the consumers' showrooming behaviour along with perceived ease purchasing online and the overall usefulness of the showrooming sequence. Results of the study revealed that the showrooming sequence helped consumers avoid the regret of making suboptimal product choices and paying a higher price for the same product. Online trust was found to partially mediate the relationship between consumers' intention to showrooming and the actual showrooming behaviour. Research limitations/implications: Notwithstanding the fact that further research is required to arrive at definitive conclusions, this study is an initial move towards understanding the consumers' showrooming behaviour, and the research provides meaningful insights. Practical implications: As showrooming substantially erodes profits, devising strategies to defend showrooming customers becomes crucial. The findings of the study provide the basis for formulating strategies to counter showrooming customers. Originality/value: The paper is amongst the first studies which helps enhance the understanding of consumers' showrooming behaviour, which is an emerging area in the present multi-channel retailing environment.